(untitled) (Revista de Ciências Agroveterinárias, 2017)
This work aimed to study alternatives to the chemical management of italian ryegrass (Lolium multiflorum), taking into account environmental and biological factors at the time of herbicide application, as well as the possible differential response among biotypes of the species. The objective of this study was to evaluate the influence of air temperature on the chemical control of two ryegrass biotypes. The experiment was conducted in a greenhouse, in a completely randomized design with four replicates and organized in a 2x2x10 factorial scheme (biotype, temperature and herbicide). One biotype was obtained from an area with annual crops and the other from a perennial crop. The tested herbicides were: clethodim, clodinafop-propargyl, fenoxaprop-p-ethyl+clethodim, glyphosate, iodosulfuron-methyl, paraquat, paraquat+diuron, sethoxydim and tepraloxydim. The application occurred in plants maintained in air temperature of 20-22 °C and 30-34 °C. The control was evaluated at 7, 14, 21 and 28 days after application of the treatments, assigning the percentage of 0 to 100 that corresponded to the absence of injury and death of the plants, respectively. The data was submitted to analysis of variance and the means were compared by the Tukey test (P=0.05). In general, herbicides were more effective at a temperature of 20-22 °C, and the temperature of 30-34 °C impaired ryegrass control. The susceptibility to the grass killers was dependent on the biotype in application under temperature of 30-34 °C.